Jurisdiction and prosecution of halal related matters in Malaysia: challenges and prospects - Che Mohd Zain, Che Rosmawati; Ab Rahman, Suhaimi; Mohd Ishan, Zahira; Ab Aziz, Shamrahayu (Elsevier, 2015)
Malaysia is planning to be a global halal hub country in the near future. However, it must be noted that administration of halal related matters in this country is yet to be an efficient one especially when it comes to legal issues of prosecution and jurisdiction. This paper explores the conceptual arguments of the two legal issues particularly its challenges and prospects in strengthening halal related matters in the country. This conceptual paper highlights factors that could improve the jurisdiction and prosecution of halal related matters in the country.